Optimasi Parameter Proses Injeksi Molding Material Biokomposit Serat Sisal dan Polypropylene Terhadap kekuatan Impak - Tsany, Rahmat Basya Shahrys; Sholihah, Mar’atus; Fajardini, Ridhani Anita; Ahmad, Mahasin Maulana; Ilman, Abdillah Fashiha; Maulidhia, Alief Nur Aisyi (Jurnal Optimalisasi, 2025)
The demand for environmentally friendly materials has driven the utilization of natural fiber–based biocomposites as an alternative engineering material. This study aims to optimize the injection molding process parameters of polypropylene (PP)–sisal fiber biocomposites with the aid of maleic anhydride polypropylene (MAPP) as a compatibilizer. The research scope covers the effect of process parameter variations on the mechanical properties, particularly impact strength. The composite material consists of 85% PP, 10% sisal fiber, and 5% MAPP, which were extruded into pellets prior to processing using an injection molding machine. Optimization was carried out using the Taguchi method with an L9 (3⁴) orthogonal array design. Four main parameters were investigated: barrel temperature (200°C, 210°C, 220 °C), injection pressure (50 bar, 55 bar, 60 bar), holding pressure (40 bar, 45 bar, 50 bar), and injection velocity (60 mm/s, 65 mm/s, 70 mm/s). The response variable was impact strength (kJ/m²) according to ASTM D256-04 standards, while other parameters were kept constant. Data were analyzed using the Signal-to-Noise Ratio (S/N ratio) with the “larger-the-better” criterion to obtain the optimum condition. The results showed that the optimum parameter combination A1B3C3D2 (200 °C, 60 bar, 50 bar, 65 mm/s) provided the best response, as this combination yielded the highest Signal-to-Noise ratio with a more stable impact performance. Under these conditions, the material flowed well into the mold, fiber distribution was uniform, and stronger bonding occurred between fiber and matrix, thereby enhancing the mechanical properties.